Pengaruh Penggunaan Teknologi Informasi Dan Pelatihan Penyidik/ Penyidik Pembantu Terhadap Optimalisasi Pemanfaatan Aplikasi E-Manajemen Penyidikan - Arnie Herdiyathi; Jarot Prianggono (Prisani Cendekia, 2022)
Polri has an important role in law enforcement, so that Polri members are required to be able to solve problems that exist around the community. This study aims to analyze the influence of the use of information technology and training on the utilization of E-MP applications, how the performance of the linear regression model using RMSE generated from this study. The research was conducted using quantitative methods with data collection techniques by means of a questionnaire. The research sample amounted to 119 people who are members of the Dirtipidum Bareskrim Polri. The data analysis technique uses validity and reliability tests, classical assumption tests, hypothesis tests and linear regression performance tests. The results of the study indicate that the use of information technology and training of investigators/assistant investigators has an effect on Optimizing the Utilization of Investigation E-Management Applications. From the test results, it is known that 73.4% of the use of information technology and the training of investigators/assistant investigators affect the use of the E-MP application